Research and application of pressure relief and permeability improvement in high gas outburst mines by directional drilling and hydraulic jet - Li, Dingqi; Chen, Yubo; Zhang, Jiabao; Wang, Mingzhong (Frontiers in Earth Science, 2023)
Abstract: Efficient gas extraction technology is an important topic for low permeability and high gas outburst coal seam. Based on the engineering background of Hudi Coal Mine with the soft and hard coal seams and the existing hydraulic permeability enhancement technology, a new construction process to improve coal seam permeability was proposed to effectively reduce coal seam gas content and the risk of coal and gas outburst. In this measure, the roadway in floor was replaced with a directional main borehole, directional branch boreholes were used to replace crossing holes, and soft coal was mined along soft sub layers via the directional drilling machine and directional hydraulic jet. Main boreholes are drilled parallel to the seam in the coal seam floor, and branch boreholes are drilled through the floor and coal seam. The numerical simulation was used to study the permeability improvement effect of different mining diameters by the proposed measure. The result showed that, as the mining diameter increased from 2m to 4m, the average influence diameter of coal seam porosity increased from 15.44m to 19.65m, and the average influence diameter of the permeability increased from 15.75m to 20.07m, which is 3 times the influence range of the ordinary borehole. The application of the proposed measure and its supporting equipment was carried out under the special coal seam and gas conditions of Hudi Coal Mine. Results show that the soft coal was mined efficiently along the soft sub layer using the main borehole, branch boreholes, and directional hydraulic jet. Compared the traditional hydraulic flushing in the borehole with the ordinary drilling machine, the average speed of mining soft sub layers increased from 0.5 t/h to 3.6 t/h, the equivalent mining diameter of soft sub layers increased from 1.2 m to 7.6 m, and the average flow of gas extraction increased from 0.41 m3/d to 6.25 m3/d. The conclusions obtained in this study can provide a reference for coal mine gas extraction with similar coal seam conditions.